P-Convexity Property in Musielak-Orlicz Function Space of Bohner Type - Romadiastri, Yulia (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2017)
In this paper, we described about Musielak-Orlicz function spaces of Bochner type. It has been obtained that Musielak-Orlicz function space of Bochner type becomes a Banach space. It is described also about P-convexity of Musielak-Orlicz function space of Bochner type. It is proved that the Musielak-Orlicz function space of Bochner type is P-convex if and only if both spaces and X are P-convex.Â©2017 JNSMR UIN Walisongo. All rights reserved.